Creepy crawlies and the scientific method : over 100 hands-on science experiments for children - Kneidel, Sally Stenhouse (Golden, Colo. : Fulcrum Pub., 1992)
Shows how to teach children ages 5-12 the five steps of the scientific method.
Includes bibliographical references (p. 213-215) and index.
Professional
Keywords: Animals -- Experiments -- Juvenile literature; Science -- Methodology -- Juvenile literature; Animals -- Experiments; Science -- Methodology